LEGAL STANDING OF FINANCIAL SERVICES AUTHORITY (FSA) AS SUPERVISION OF BANKS INSTITUTIONS IN INDONESIA - Zulfi Diane Zaini; Tami Rusli (International Conference On Law, Business and Governance (ICon-LBG), 2016)
The presence of Financial Services Authority (FSA) in the development of the financial sector in Indonesia is expected to help the activities of financial institutions, especially in banking, so that the regulation of financial services activities can be implemented well and have a positive impact for economic development in Indonesia. The weakness of bank supervision is one of the main causes of mismanagement bank that eventually led to bank failures. Bank has a special position as an institution of trust as its main business is to funding from and lend to the public. The problem in this research is how the legal standing of FSA in performing its functions as the National Institute of Banking Supervisors of the economic development of Indonesia? and How Legal Relationship between the FSA and Bank Indonesia as the Central Bank in Indonesia?.The research method used is Juridical Normative and Empirical Approach, The data used is secondary and primary data,analysis of the data used is Juridical Qualitative. Based on the results of research it is known that, Legal Standing of FSA is an Independent Institute, organized regulation and supervision of banking macroprudentialsystem. Regulation and supervision of the institutional, health, aspects of prudential and bank checks is a scope of the regulation and micro prudential supervision of the duties and authority of the FSA. Legal Relationship between the FSA and Bank Indonesia as the Central Bank in Indonesia, perform coordination and cooperation with Bank Indonesia, especially in terms of handling Problem Bank in line with Bank Indonesia function as a lender of last resort, in the case of the FSA indicates certain banks experiencing liquidity difficulties and/or worsen health conditions, FSA inform the Bank Indonesia to take steps in accordance with the authority of Bank Indonesia.